1996
DOI: 10.1128/aem.62.10.3885-3886.1996
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and isolation of a nitropropanol-metabolizing bacterium from the rumen

Abstract: A bacterium capable of metabolizing nitropropanol, nitropropionate, and nitrate has been isolated from a mixed ruminal population enriched for enhanced rates of nitropropanol metabolism. The numbers of nitropropanol-metabolizing bacteria in mixed populations increased >10,000-fold during enrichment; the rates of nitropropanol metabolism increased 8-fold. Hydrogen and phytone were important nutrients for nitropropanol metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Assuming that each micromole of NPA or NPOH reduced consumes six electrons or the equivalent of 3 μmol of hydrogen, based on stoichiometric estimates for the reduction of nitroethane by a Clostridium pasteurianum hydrogenase/ferredoxin system ( 50 ), the NPA and NPOH metabolized in this study would have consumed at most only 4.2 and 7.8 μmol hydrogen equivalents/mL, respectively. The lesser amounts of NPA and NPOH metabolized within the mixed cultures incubated with NPA- and NPOH-containing milkvetch incubations in experiment 1, which were not inoculated with D. detoxificans is not surprising, considering that D. detoxificans is usually present at low concentrations (<10 4 cells/mL) in rumen populations having no prior nitrocompound exposure ( 51 ). Based on these considerations, the more potent methane-inhibiting effect observed in the mixed cultures inoculated with D. detoxificans and incubated with the NPOH-containing milkvetch cannot be explained solely by competitive consumption of reducing substrates for the reduction of NPOH.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that each micromole of NPA or NPOH reduced consumes six electrons or the equivalent of 3 μmol of hydrogen, based on stoichiometric estimates for the reduction of nitroethane by a Clostridium pasteurianum hydrogenase/ferredoxin system ( 50 ), the NPA and NPOH metabolized in this study would have consumed at most only 4.2 and 7.8 μmol hydrogen equivalents/mL, respectively. The lesser amounts of NPA and NPOH metabolized within the mixed cultures incubated with NPA- and NPOH-containing milkvetch incubations in experiment 1, which were not inoculated with D. detoxificans is not surprising, considering that D. detoxificans is usually present at low concentrations (<10 4 cells/mL) in rumen populations having no prior nitrocompound exposure ( 51 ). Based on these considerations, the more potent methane-inhibiting effect observed in the mixed cultures inoculated with D. detoxificans and incubated with the NPOH-containing milkvetch cannot be explained solely by competitive consumption of reducing substrates for the reduction of NPOH.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the ruminal bacterium Denitrobacterium detoxificans is the only known anaerobe to exhibit appreciable nitroalkane-reducing activity (Anderson et al, 1996 , 1997 , 2000 ). This bacterium conserves energy for growth exclusively via anaerobic respiration, oxidizing hydrogen, formate or lactate in the reduction of nitrate to ammonia and the reduction of 3-nitro-1-propionic acid, 3-nitro-1-propanol, and nitroethane to β-alanine, 3-amino-1-propanol and aminoethane, respectively (Anderson et al, 1993 , 1997 , 2000 ).…”
Section: Nitrocompound Metabolism Within the Rumenmentioning
confidence: 99%
“…Majak and Cheng [18] in an earlier study with both pure and mixed cultures confirmed that some rumen bacteria were indeed capable of anerobic degradation of naturally occurring 3-nitropropanol or 3-nitropropionic acid, and the ability to degrade these nitrocompounds and the rate at which they were degraded depended essentially on the particular strains of rumen bacteria (e.g., Megasphaera elsdenii, Selenomonas ruminantium). In subsequent studies, a new bacterium capable of metabolizing the naturally occurring nitrotoxins, 3-nitro-1-propanol and 3-nitro-1-propionate, was isolated from a ruminal population enriched for enhanced rates of nitrotoxin metabolism [19] and was accommodated as Denitrobacterium detoxificans, a new genus and species capable of degrading nitrocompounds into nitrite and then ammonia [20,21]. Although the present study was done with mixed cultures instead of pure culture, rumen microbes should have more or less similar degradation or metabolic action to NE, NEOH, and NPOH, like the 3-nitro-1-propanol and 3-nitro-1-propionate noted in the aforementioned studies.…”
Section: Nitrocompounds' Degradation and Metabolic Fatementioning
confidence: 99%